Fighting terror with law? Some other genealogies of pre-emption - Mark Finnane (International Journal for Crime, Justice and Social Democracy, 2013)
Within criminology and criminal law the reception of post-9/11 counter-terrorist law has generally been critical, if not hostile. The undeniable proliferation of preventive statutes has been regarded as incompatible with conventional liberal norms and as dangerously innovative in its embrace of new strategies of control. But is such law innovative, and does it threaten to leach into other areas of criminal law, as some have feared? Exploring three governmental innovations – mental health law, habitual criminal controls, and civilian internment in war-time – that developed as expressions of the liberal state’s desire to ensure the safety of its citizens in times of peace and war, the authors argue that a more historically grounded understanding of the governmental and geopolitical contexts of security provides a surer foundation on which to construct the frameworks of interpretation of contemporary counter-terrorism law